2022
DOI: 10.1093/emph/eoac019
|View full text |Cite
|
Sign up to set email alerts
|

Different predictors of intimate partner and natal family violence against women

Abstract: Background Violence against women is often studied in the context of violence from intimate partners. However, women receive violence from a wider range of individuals—such as their natal kin—including their siblings, parents, uncles, and cousins. Applying insights from evolutionary theory we examine whether cousin marriage, which has been hypothesised to both reduce the risk of partner violence but increase the risk of natal family violence, associates differently with each type of violence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Conversely, women concentrated in the community with high women decision-making autonomy have a high probability of encountering PIPV. This suggests that as women gain autonomy, they struggle for reproductive autonomy, including fertility control, which can lead to PIPV victimization in traditional societies where men hold primary decision-making power in marriage, as evidenced by other studies [59][60][61] . Also, the result is consistent with a cohort study conducted in Nepal, which found that the risk of contracting IPV was higher in women who became pregnant and gave birth than in those who did not 62 .…”
Section: Discussionmentioning
confidence: 93%
“…Conversely, women concentrated in the community with high women decision-making autonomy have a high probability of encountering PIPV. This suggests that as women gain autonomy, they struggle for reproductive autonomy, including fertility control, which can lead to PIPV victimization in traditional societies where men hold primary decision-making power in marriage, as evidenced by other studies [59][60][61] . Also, the result is consistent with a cohort study conducted in Nepal, which found that the risk of contracting IPV was higher in women who became pregnant and gave birth than in those who did not 62 .…”
Section: Discussionmentioning
confidence: 93%
“…Some researchers associate polygynous family arrangements—a key feature of traditional African societies—to women’s risk of IPV (Amo-Adjei and Tuoyire 2016; Behrman 2019; Jansen and Agadjanian 2020; Tenkorang 2023). Others suggest ethnic and lineage ties increase women’s risks of experiencing IPV (Asiedu 2016; Campbell and Mace 2022; Lowes 2016; Sedziafa and Tenkorang 2016; Sitawa, Tenkorang, and Djamba 2018). For instance, using data collected in Kananga, the capital of Kasai Central Province in the Democratic Republic of Congo, Lowes (2020a) found women in matrilineal societies experienced less domestic violence and had higher autonomy.…”
Section: Introductionmentioning
confidence: 99%